NOVASI DAN CESSIE VERSUS HAWALAH MELALUI KONTRAK: KAJIAN UNTUNG RUGI DAN DALAM PEMBIAYAAN TAKE OVER DALAM KUH PERDATA DAN KHES - Hidayat, Rahmat; Harahap, Mhd. Yadi; Lubis, Fauziah (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
This study examines a comparative analysis of the mechanisms of novation, cession, and hawalah in take-over financing practices from the perspectives of the Indonesian Civil Code (KUH Perdata) and the Compilation of Sharia Economic Law (KHES). The main focus is directed toward analyzing profit and loss from three dimensions: economic, administrative, and sharia compliance. Methodologically, this research employs a normative legal approach using statutory and conceptual analyses, supported by secondary data sources such as regulations, DSN-MUI fatwas, academic literature, and doctrines of contract law. The findings indicate that economically, novation and cession offer flexibility and potential benefits for financial institutions because they allow rapid restructuring or transfer of receivables. However, both mechanisms may impose additional financial burdens and potential value imbalances on debtors. Administratively, novation and cession have the advantage of stronger legal certainty due to their execution through authentic deeds, whereas hawalah is more efficient and simpler to implement but has weaknesses in terms of formal evidentiary strength. From a sharia perspective, hawalah is considered the most compliant with principles of justice and propriety because it does not contain elements of riba or gharar, thereby better reflecting the value of ta'awun (mutual assistance).